Decentralization and Public Services : The Case of Immunization - Khaleghian, Peyvand (World Bank, Washington, DC, 2014)
The author studies the impact of political decentralization on childhood immunization, an essential public service provided in almost all countries. He examines the relationship empirically using a time-series data set of 140 low- and middle-income countries from 1980 to 1997. The author finds that decentralization has different effects in low- and middle-income countries. In the low-income group, decentralized countries have higher coverage rates than centralized ones, with an average difference of 8.5 percent for measles and DTP3 vaccines. In the middle-income group, the reverse effect is observed: decentralized countries have lower coverage rates than centralized ones, with an average difference of 5.2 percent for the same vaccines. Both results are significant at the 99 percent level. Modifiers of the decentralization-immunization relationship also differ in the two groups. In the low-income group, development assistance reduces the gains from decentralization. In the middle-income group, democratic government mitigates the negative effects of decentralization, and decentralization reverses the negative effects of ethnic tension and ethno-linguistic fractionalization, but institutional quality and literacy rates have no interactive effect either way. Similar results are obtained whether decentralization is measured with a dichotomous categorical variable or with more specific measures of fiscal decentralization. The study confirms predictions in the theoretical literature about the negative impact of local political control on services that have public goods characteristics and inter-jurisdictional externalities. The author discusses reasons for the difference between low- and middle-income countries.